Implementation of Organizational Communication in the Formation of Socio-Religiopreneurship at PT Mentari Prima Niaga - Syauqi Soeratno, Ahmad; Kirana Jaya, Wihana; Ahmad, Nyarwi; Ikhwan, Hakimul (COMMICAST, 2025)
In the modern business world, socio-religiopreneurship is an approach that integrates Islamic values with business practices, creating a balance between economic profit and social benefits. As part of the Muhammadiyah Charity, PT Mentari Prima Niaga applies this concept in its business operations. This research aims to analyze the organizational communication strategy used by PT Mentari Prima Niaga in implementing socio-religiopreneurship to understand how communication can support the sustainability of Islamic value-based businesses. The research method used is a qualitative approach with a case study, where data is collected through interviews, observations, and document analysis. The results showed that PT Mentari Prima Niaga implemented a value-based communication strategy, two-way communication, and digital technology to improve organizational synergy. The main barriers in organizational communication include continually improving the understanding of Islamic values among employees, missing communication in the workplace, and sometimes the lack of effective communication channels in certain situations. The company overcomes these barriers through intensive training programs and strengthening internal communication procedures. The results of this study provide implications for companies that want to implement socio-religiopreneurship with effective communication strategies. In addition, this research also provides insights for Islamic-based business institutions in optimizing organizational communication to achieve economic and social welfare sustainably.